Short-term effects of whole-body vibration on maximal voluntary isometric knee extensor force and rate of force rise - de Ruiter, C. J.; van der Linden, R. M.; van der Zijden, M. J. A.; Hollander, A. P.; de Haan, A. (European Journal of Applied Physiology, 2003)
Whole-Body vibration (WBV) may lead to muscle contractions via reflex activation of the primary muscle spindle (Ia) fibres. WBV has been reported to increase muscle power in the short term by improved muscle activation. The present study set out to investigate the acute effects of a standard WBV training session on voluntary activation during maximal isometric force production (MVC) and maximal rate of force rise (MRFR) of the knee extensors. Twelve students underwent a single standard WBV training session: 5·1 min vibration (frequency 30 Hz, amplitude 8 mm) with 2 min rest in between. During vibration, subjects stood barefoot on the vibration platform with their knees at an angle of 110°. At 90 s following vibration, maximal voluntary knee extensor force was reduced to 93 (5)% [mean (SD), P<0.05] of baseline value and recovered within the next 3 h. Voluntary activation remained significantly depressed (2-4%). Neither the electrically induced MRFR nor voluntary MRFR were significantly affected by WBV. In addition, six WBV training sessions in 2 weeks (n=10) did not enhance either voluntary muscle activation during MVC [99 (2)% of the baseline value] or voluntary MRFR [98 (9)% of the baseline value]. It is concluded that in the short term, WBV training does not improve muscle activation during maximal isometric knee extensor force production and maximal rate of force rise in healthy untrained students.